The Titanic in print and on screen : an annotated guide to books, films, television shows, and other media - Anderson, D. Brian (McFarland & Co., 2005)
"This bibliography is a survey of the volume of literary, dramatic and commercial endeavors that came out of history's most compelling shipwreck. Organized by genre in accessible categories and short entries, the book includes Titanic-inspired documentaries, narrative films, children's books, histories, short stories, novels, plays, articles, essays, software, websites, poems and songs"--Provided by publisher